Aquatic entomofauna from Gorgona National Natural Park, Colombian Pacific, with emphasis in Ephemeroptera and Plecoptera - Zuñiga, María del Carmen (2014)
Gorgona is a Colombian continental island that biogeographically belongs in the Choco region. This work constitutes a first approximation to the aquatic insects, with emphasis in Ephemeroptera and Plecoptera: distribution, ecology, and associations to the continental mainland. Between October 2010 and June 2011, immature and adult specimens were collected in five streams of the island´s Western sector using entomological nets, Malaise traps, and light traps. A total of nine orders, 28 families, 39 genera and 16 species of aquatic insects were found. New geographical records for Gorgona include: Dytiscidae (Coleoptera), Zelusia, Farrodes and Terpides (Ephemeroptera), Leucotrichia and Wormaldia (Trichoptera), Laccodytes, Neoelmis and Pheneps (Coleoptera), Maruina and Limonia (Diptera). As part of this study, four new species for each, Ephemeroptera and Plecoptera, were found. Leptohyphes jodiannae, L. maculatus and Hagenulopsis esmeralda are recorded for the first time for Colombia. Farrodes caribbianus, F. roundsi, Hagenulopsis zunigae, Zelusia principalis and Anacroneuria choco are reported for the first time for the National Park. The high abundance of families, genera, and species is similar to that of low order streams in the tropic mainland, particularly those associated to the Choco bio-geographical province. Rev. Biol. Trop. 62 (Suppl. 1): 221-241. Epub 2014 February 01.